Symbiotic and Regenerative Sustainability Frameworks: Moving Towards Circular City Implementation - Horn, Erin; Proksch, Gundula (Frontiers in Built Environment, 2022)
Growing in popularity, the circular city framework is at the leading-edge of a larger and older transitional dialogue which envisions regenerative, circular, and symbiotic systems as the future of urban sustainability. The need for more research supporting the implementation of such concepts has been often noted in literature. To help address this gap, this holistic review assesses a range of pertinent sustainability frameworks as a platform to identify actionable strategies which can be leveraged to support and implement circular city goals. This assessment is grounded in a holistic overview of related frameworks across interdisciplinary and scalar domains including circular city, the food-water-energy nexus, circular economy, bioeconomy, industrial symbiosis, regenerative design, and others. Building on these interrelationships, the applied strategies espoused within these publications are synthesized and assessed in the context of circular city implementation. From an initial 250 strategies identified in literature, thirty-four general implementation strategies across six thematic areas are distinguished and discussed, finding strong overlaps in implementation strategies between frameworks, and opportunities to further develop and harness these synergies to advance circular city toward sustainable urban futures.